Identification of a Latin American-specific BabA adhesin variant through whole genome sequencing of Helicobacter pylori patient isolates from Nicaragua. Issue 1 (December 2016) - Thorell, Kaisa; Hosseini, Shaghayegh; Palacios Gonzáles, Reyna; Chaotham, Chatchai; Graham, David; Paszat, Lawrence; Rabeneck, Linda; Lundin, Samuel; Nookaew, Intawat; Sjöling, Åsa
Abstract Background Helicobacter pylori (H. pylori) is one of the most common bacterial infections in humans and this infection can lead to gastric ulcers and gastric cancer.H. pylori is one of the most genetically variable human pathogens and the ability of the bacterium to bind to the host epithelium as well as the presence of different virulence factors and genetic variants within these genes have been associated with disease severity. Nicaragua has particularly high gastric cancer incidence and we therefore studied Nicaraguan clinicalH. pylori isolates for factors that could contribute to cancer risk. Methods The complete genomes of fifty-two NicaraguanH. pylori isolates were sequenced and assembledde novo, and phylogenetic and virulence factor analyses were performed. Results The Nicaraguan isolates showed phylogenetic relationship with West African isolates in whole-genome sequence comparisons and with Western and urban South- and Central American isolates using MLSA (Multi-locus sequence analysis). A majority, 77 % of the isolates carried the cancer-associated virulence genecagA and also the s1/i1/m1 vacuolating cytotoxin, vacA allele combination, which is linked to increased severity of disease. Specifically, we also found that Nicaraguan isolates have a blood group-binding adhesin (BabA) variant highly similar to previously reported BabA sequences from Latin America, including from isolates belonging to other phylogenetic groups. These BabA sequences were found to be under positive selection at several amino acid positions that differed from the global collection of isolates. Conclusion The discovery of a Latin American BabA variant, independent of overall phylogenetic background, suggests hitherto unknown host or environmental factors within the Latin American population givingH. pylori isolates carrying this adhesin variant a selective advantage, which could affect pathogenesis and risk for sequelae through specific adherence properties.